"Communication in political discourse "body as a model - Ebah, Magda (Arab Journal for Sciences and Research Publishing, 2015)
The study is concerned with highlighting the role of the body in political discourse, which provides countless signs, extends in all aspects of life, and produces countless gestures, it is the identity which characterizes us, and we recognize through it, and the interface that shapes speech and progress. Hence, the importance of knowledge of its preparation, to be included within the bodies of successful, and active in society. As his presence was strong, attempts to approach him, to deal with him, and to engage him, appeared to discover his strengths. How can this be achieved? How can the power of the body affect the political decision? Political discourse, however, is not considered a beautiful body (as in sports advertising) nor is it a soft hair or a shiny complexion (as we see in cosmetics).